Handbook of human performance. - Jones, D. M. (Dylan M.); Smith, A. P. (Andrew P.) (Academic Press, 1992)
This volume covers such issues as sound and vibration, the thermal environment, and the visual environment. It contains conmmentaries from the leading authorities in the field.